(untitled) (Journal of the College of Basic Education, 2022)
Searching for the aesthetic distance in the theatrical performance directed at the child means searching inThe process of interaction between the presenter and the recipient/child. The result leads to knowing the importance of distanceAesthetics and control over its extent. The extent of integration/separation in the theatrical show is determined by:According to the director’s style, treatment, and childish vision of the text and the available production capabilities.The research sheds light on how to separate the real from the imaginary in theatrical performanceOriented to the child, because the child as a recipient needs a clear aesthetic distance more than the adultDimensions during his reception of arts and literature in general and theatrical performance in particular because heLive show.